Case study: Short‐term response of greater sage‐grouse habitats to wildfire in mountain big sagebrush communities. (18th December 2014) - Davis, Dawn M.; Crawford, John A.
ABSTRACT: Our case study evaluated the short‐term (≤11 yr) implications of wildfire on greater sage‐grouse ( Centrocercus urophasianus ) breeding‐season habitat (i.e., nesting and brood‐rearing) and ground‐dwelling arthropod abundance on Sheldon National Wildlife Refuge in northwestern Nevada, USA. Two different‐aged wildfire sites were sampled in mountain big sagebrush ( Artemisia tridentata vaseyana ) cover types in 1998 and 1999. Plant communities in burned and associated unburned areas did not differ appreciably in species composition and wildfire did not negatively impact arthropod abundance. Wildfires did not increase the frequency of exotic plant species, such as cheatgrass ( Bromus tectorum ), nor did wildfire have a detrimental effect on native perennial bunchgrasses. Wildfires were effective at changing the mountain big sagebrush community structure from shrub‐dominated to one dominated by native grasses and forbs 2–3 yr post‐burn. However, the absence of shrub cover following 2–3 yr of post‐fire recovery indicates our overall estimates of vegetation structure were not consistent with published guideline requirements for managing sage‐grouse breeding‐season habitat. Although burning had little stimulatory effect on total forb cover 10–11 yr post‐burn, the vegetation and structural components needed to maintain suitable sage‐grouse nesting and brood‐rearing habitats were present in the burned site. The short‐term habitat response to wildfire suggests prescribed fire can be a useful tool to achieve management objectives by manipulating vegetation structure and composition of shrub‐dominated landscapes. However, land managers should be cautious using prescribed fire as a management tool in big sagebrush ecosystems if the goal is to improve sage‐grouse habitats. © 2014 The Wildlife Society.